THE EFFECTS OF CONTEXTUAL TEACHING AND LEARNING ( CTL ) ‘INQUIRY’ ON THE LEARNING ACHIEVEMENT OF LITERATURE APPRECIATION AT THE EIGHTH GRADERS OF SMPN 3 TERARA - Zainul Muttaqin; Anggraini Dwi Cahya (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2019)
This study aimed to: 1) finding out if CTL is effective in the studensts learning achievment in Indonesian subject matter with “litterature appreciation” basic competence of the eight grade of SMPN 3 Terara; and 2) describing the differences between using CTL and convensional teaching. This study was a quasy-experiment with pretest postest non equivalent group design. The populatian was the eight graders of SMPN 3 Terara. The sample was taken purposively. Chi-square and variance homogenitywere done to see the varience of the two groups. The hyphotesis was done throught one sample t-test and t test . the result showed that CTL was effective in the learning achievement of the eight graders of SMPN 3 Terara.